PENGARUH PEMBERIAN CENDAWAN ENTOMOPATOGEN (Beauveria bassiana) TERHADAP TINGKAT SERANGAN HAMA PRODUKSI PADA TANAMAN TOMAT (Lycopercicum esculentum mill) - Marhani, Marhani (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
Influence Giving Entomopatogen Fungus Beauveria bassiana on Pest Attack Rate and Growth and Production on Tomato Plant (Lycopercicum esculentum Mill). This study aims to determine the effect and dose of Entomopatogen Beef Entomopatogen bassiana to the level of pests and the growth and production of tomato plants (Lycopercicum Esculentum mill.)This research was conducted for 4 months from January to April 2017 located at Jalan Pembagunan Kecamatan Long Mesangat, East Kutai Regency. Using Group Random Design (RAK) consisting of 4 treatments The treatment is: B0 = Control B1 = Beauveria bassiana 2 gr / ltr, B2 = Beauveria bassiana 4 gr / ltr, B3 = Beauveria bassiana 6 gr / ltr. To know the effect of treatment then do the analysis of variance and if there is a real influence then proceed with BNT test level 5%.The results showed that the treatment of fungus beauveria bassiana had a very significant effect on the emphasis of pest attack rate, growth increase, flowering age and production of tomato plants at various observations. Dose 6 grams / liter of water beauveria bassiana is the best treatment in suppressing the level of pest attack 14 HST (15.23%), 28 HST (20.37%), 42 HST (11.84%). Increased number of leaves 14 HST (53.65 strands), 28 HST (89.28 strands), 42 HST (141.46 strands). Acceleration of flowering age 25.33 days. The weight of fruit is 172.5 kg and the production rate is 9.79 tons / ha. Keywords: Fungi Beauveria bassiana, Pest. Tomato